Beyond Beliefs: Integrating Cultural Practices, Family Dynamics, and Ecological Vulnerabilities in Explaining Childhood Malnutrition in Indonesia - Masita, Elly Dwi; Munjidah, Annif; Dewi, Uke Maharani; Novianti, Hinda (International Journal of Child Health and Nutrition, 2026)
Childhood malnutrition remains a major public health issue in Indonesia, with prevalence in some communities reaching 68.2%, far above the national average. Despite multiple government programmes, progress has been limited. Previous studies have primarily examined biomedical or socioeconomic factors, while less attention has been given to how cultural beliefs, ecological vulnerabilities, and familial decision-making interact to shape nutritional outcomes. This gap constrains the design of effective interventions. A cross-sectional mixed-methods study was conducted in rural East Java among 179 caregivers of children aged 1-5 years. Nutritional status was assessed using weight-for-age (<90% of the WHO median defined as malnutrition). Quantitative analyses included descriptive statistics, independent t-tests, and logistic regression with diagnostic checks. Qualitative interviews explored beliefs about feeding, food taboos, ecological barriers, and household decision-making. Findings were integrated using triangulation. Malnutrition prevalence was 68.2%. Independent t-tests revealed significant differences in Health Belief Model (HBM), cultural integration, and ecological scores between malnourished and adequately nourished children (p<0.05). Logistic regression, however, did not retain any variable as an independent predictor (Hosmer-Lemeshow p=0.411, Nagelkerke R²=0.115, AUC=0.669). Qualitative data explained these contradictions, highlighting systemic poverty, food scarcity, weak health service outreach, and intergenerational authority as key barriers despite caregiver knowledge. Malnutrition in Indonesia is shaped by the convergence of cultural, ecological, and familial determinants rather than single risk factors. Effective responses must integrate culturally sensitive behaviour change with structural support, address ecological vulnerabilities, and engage family decision-making. Mixed-methods approaches are essential to capture the complexity of these interactions.